EVALUATION OF THE GROUNDWATER QUALITY IN A CLOSED INDUSTRIAL LANDFILL - SENOU ISSAKA; NARCIS BÂRSAN; VALENTIN NEDEFF; SOME N. ANTOINE; NACRO H. BISMARCK (Journal of Engineering Studies and Research)
The study parameters: pH, conductivity, salinity, Total Dissolved Solids (TDS), Turbidity, Total Suspended Solids (TSS) and Chemical Oxygen Demand (COD) of groundwater in a closed industrial landfill, subject to the waste discharges of city of Bacau (East Romania), shows that the water quality of the different sampling points is variable. This difference is noted at the level of conductivity, TDS, turbidity, TSS and COD. These differences, however parameters are substantially higher compared the value of the legislation in groundwater Romania. Salinity remains relatively high at the point of sample P1 (0.7). The pH values are comprising in the range of reference values (6.5 to 7.4). The results also showed very strong correlations (r> 0.8) between Conductivity-Salinity, Conductivity -TDS, Salinity, TDS, Turbidity.-TSS, COD and TSS-Turbidity-COD. The strong correlation (0.5 0.8) were noted between Turbidity- Conductivity, Turbidity-Salinity, Turbidity, TDS, TSS conductivity, TSS-Salinity, TSS, TDS, COD, conductivity, salinity, COD, COD-TDS. Principal Component Analysis (PCA) also highlighted groundwater mineralization events of this landfill and possible pollution by organic matter.